Profil Usaha Industri Susu Kedelai UD. Tiga Bersaudara Di Kecamatan Tikala Kota Manado - Dina Ekawati Hungopa; Ribka M. Kumaat; Lorraine W. Th. Sondakh (Sam Ratulangi University, 2016)
This study aimed to describe the Profile of the Soy Milk Industry Enterprises UD. Three Brothers in Sub-district of Tikala, Manado City, seen from the Organizational Structure, raw material procurement, production costs, marketing and profit. The research was conducted from preparation in June until the completion of the report in September 2016. This research was used primary data and secondary data. The primary data obtained through interviews using questionnaires to the owners of the soy milk industry UD Three Brothers in Sub-district of Tikala, Manado City. Primary data collected has studied and analyzed descriptively and presented in tabular form. The results showed that soy milk UD. Three Brothers is packaged in two packages, namely, bottles and packaging wrap. Soy milk is marketed to five places, namely, Freshmart, Golden, Market Karombasan, X.O and Noodle Medan 88, with the price for one bottle and a pack of Rp. 5000.- respectively. Industrial soy milk UD. Three Brothers survived until today because of their perseverance, patience and entrepreneurial spirit of the industry owners.